Synthesis, characterization and X-ray structural, electrochemical and Mössbauer study of mercury(II) complexes with 1′-(diphenylphosphino)ferrocenecarboxylic acid - Štěpnička, Petr; Cı́sařová, Ivana; Podlaha, Jaroslav; Ludvı́k, Jiřı́; Nejezchleba, Martin (Journal of organometallic chemistry, 1999)
Reaction of mercury(II) halides with 1′-(diphenylphosphino)ferrocenecarboxylic acid (Hdpf) affords [HgX 2(Hdpf- P) 2] or [HgX(μ-X)(Hdpf- P)] 2 complexes (X=Cl, Br, I) depending on the stoichiometry of the educts. The complexes have been studied by IR, Mössbauer and solution NMR spectroscopy. In dimethyl sulfoxide-d 6 solution, 1H- and 31P{ 1H}-NMR spectra indicate solvolytic cleavage of the mercury(II)–phosphine bond resulting in partial decomplexation of the phosphine ligand. Electrochemical measurements in donor solvents also confirm the presence of a non-coordinated ligand since the electrochemical behavior is the superposition of that of the product of solvolysis and of the ligand. X-ray structural analysis, of the representatives of both types, was carried out: [HgBr 2(Hdpf- P) 2] ([C 46H 38Br 2Fe 2HgO 4P 2], monoclinic; space group C2/ c, a=19.453(1), b=13.704(1), c=17.929(2) Å; β=114.953(7)°; Z=4) and [HgBr(μ-Br)(Hdpf- P)] 2·2CH 3CO 2H ([C 54H 54Br 4Fe 2Hg 2O 12P 2], triclinic; space group P, a=9.442(1), b=11.7101(9), c=14.806(1) Å; α=109.692(7), β=92.494(9), γ=101.883(7)°; Z=1). The P-monodentate coordination of the phosphinocarboxylic ligand was confirmed in both cases, the carboxyl group being involved in hydrogen bonding to carboxyl groups of either neighboring ligand or solvating acetic acid. The expected Br 2 P 2 and Br 3 P tetrahedral donor sets around Hg(II) are the subject of different degrees of deformation due to steric effects. 57Fe Mössbauer spectra of the complexes also point to the P-coordination of the ferrocenylphosphino ligand, as follows from the decrease of the quadrupole splitting and only a slight variation of the isomer shift on going from ligand to complex.